Fraud Prevention: Effectiveness of Sharia Governance in Sharia Banks - Hernawati, Nopi; Maemunah, Mey; Mafruhat, Ade Yunita (KnE Social Sciences, 2024)
This research is motivated by the phenomenon of fraud that still occurs in Islamic banking, which is incidentally based on Sharia principle, which may be due to weak implementation of Shariah governance. In addition, Shariah governance can also be the key to preventing fraud. The goal that will result from this research is to assist Islamic banks in efforts to prevent fraud, namely by Sharia governance. This research is descriptive research with a quantitative approach. The data source used in this study is primary data obtained using a questionnaire filled out by internal auditors at several Islamic banks in the city of Bandung. Data collection was done using observation and documentation techniques. A non-probability sampling technique was used in this study using convenience sampling. The program used for analyzing data was Smartpls. The results of the research show that Sharia governance is good. So that the potential for fraud in financial management in Islamic Banks will decrease. Based on the results of the study, Sharia governance has a positive and significant effect on fraud prevention. Keywords: fraud prevention, Islamic banking Sharia governance